Implementing the “Show-and-Tell” Method to Improve Students’ Speaking Skills - Hasna Salsabila; Muhamad Ahsanu; Mustasyfa Thabib Kariadi; Slamet Riyadi (JELLE, 2023)
This study aimed to find out the implementation of the "show-and-tell" method, the improvement scores after using the method, and teachers' and students' perceptions toward the method. This research used a Classroom Action Research (CAR) design, which was conducted in two cycles. The data included both qualitative and quantitative data. The quantitative data were gathered from pre-test and post-test, while the qualitative data were obtained from observations and interviews. The result of this research showed that; (1) The implementation of "show-and-tell" method was successfully implemented in the teaching and learning process. It is shown by the students' feeling enthusiastic about the use of media and actively participating in the learning process. (2) Besides that, the results from pre-test to post-test 2 showed a significantly different score. In the pre-test, the mean score was 46.44, then it became 66.60 in the post-test 1, with an increase in students' scores of 20.16 (43.41%). Then, in post-test 2 the mean score increased to 76.26, with an improvement of 9.66 (14.50%). Furthermore, the result of the T-test shows that the significance value (sig. 2-tailed) was 0.00 < 0.05. It means that the implementation of the show-and-tell method to improve the students' speaking skills in the seventh grade of SMP Negeri 3 Karawang Barat had a significant effect. (3) This result is also supported by the data from the interviews with the teacher and the students. They stated that this method helped them improve their speaking skills. The teacher also said that she was satisfied with the students' speaking test scores after using the show-and-tell method in the teaching process.